Quantitative Series: Factors Analysis Effects of Government Regulation Number 46 the Year 2013 For SME’s by Justice, Convenience, and Simplicity of Tax Aspects - Aditya Halim Putra; Aan Aswari; Muhammad Ya'rif Arifin; Rina Rina (Faculty of Law, Universitas Muslim Indonesia, Indonesia, 2018)
In 2013 the business circle was struck by the new tax rules, namely Government Regulations PP No. 46, 2013 on taxation regulations among UKM (SME’s) / Small Medium Enterprises but the strong allegations issued PP 46 of 2013 is because the potential tax revenue from the sector of UKM has not been explored to the fullest. By the required by the taxpayer related PP. No. 46 of 2013 uses several variables, namely taxes, taxes, taxes and tax benefits. The object of this research is the perpetrators of UKM (SMEs) in Makassar City who do 40 people using quantitative analysis and quantitative analysis. The result of this research indicates that the perception of justice tax has a significant effect as well as the most dominant variable affecting taxpayer compliance, taxability perception has a significant adverse impact on taxpayer compliance, tax perception simplicity has no significant impact, taxpayer's judgment is not valid in testing. The overall coefficient of determination contributes 26.5%.